(untitled) (Research, Society and Development, 2021)
Man has an inherent aspiration to register his works of art since the dawn of antiquity, whose longing led to the search for natural pigments to develop paints. Natural pigments are present in all living matter and provide attractive colors, replacing synthetic dyes. In this perspective, the research deals with natural pigments and their possibilities and experiments in the artistic field, in the language of the visual arts, specifically in painting. In this context, pigments become essential for making natural, ecological paints, and can offer numerous possibilities to be transformed into art. The study aims to recognize and identify the natural pigments that exist in the Cariri region of Ceará. In this context, it is an action research, an experimental study, applied, with an exploratory and participatory approach, with the contribution of bibliographic research. Under this aegis, the natural material (mineral) was collected at Chapada do Araripe. In this case, the collection prioritized the by-products, easily accessible, as raw material in the Riacho do Meio Geopark, Barbalha-CE. Also, raw material was extracted at Lago da Misericórdia Cascata and at Sitio Fundão State Park located in Crato-CE. It is possible to think about art by developing sensitivity, recognizing art as knowledge, research and artistic creation, as well as using it in the didactic approach in schools and making students artistic.